2020
DOI: 10.3389/fnins.2020.00264
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation of the Pineal Gland via Electrical Stimulation of Its Sympathetic Innervation Pathway

Abstract: Stimulation of the pineal gland via its sympathetic innervation pathway results in the production of N-acetylserotonin and melatonin. Melatonin has many therapeutic roles and is heavily implicated in the regulation of the sleep-wake cycle. In addition, N-acetylserotonin has recently been reported to promote neurogenesis in the brain. Upregulation of these indoleamines is possible via neuromodulation of the pineal gland. This is achieved by electrical stimulation of structures or fibres in the pineal gland symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 231 publications
(331 reference statements)
0
11
0
Order By: Relevance
“…Increase in the activity of nervi conarii initiated by the suprachiasmatic nucleus of the hypothalamus stimulates the synthesis of melatonin during night time. 112 Day time melatonin levels are low. Optimal levels of melatonin is a powerful free-radical scavenger and combats oxidative stress.…”
Section: Sleep Deprivation and Melatoninmentioning
confidence: 99%
“…Increase in the activity of nervi conarii initiated by the suprachiasmatic nucleus of the hypothalamus stimulates the synthesis of melatonin during night time. 112 Day time melatonin levels are low. Optimal levels of melatonin is a powerful free-radical scavenger and combats oxidative stress.…”
Section: Sleep Deprivation and Melatoninmentioning
confidence: 99%
“…The SPNs from the IML project out to the postganglionic neurons located within the cervical sympathetic chain (Bowers et al, 1984). The postganglionic sympathetic neurons directly innervate the pineal gland and release norepinephrine during dark cycles of the circadian rhythm to stimulate melatonin synthesis (Huang and Lin, 1984;Lumsden et al, 2020).…”
Section: Pineal Glandmentioning
confidence: 99%
“…Increasing levels of melatonin has been explored as a means to treat able-bodied individuals with perturbed sleep patterns. Interestingly, it has been found that following SCI, the pineal gland is able to produce melatonin again with electrical stimulation of the sympathetic pathway responsible for innervating the pineal gland (Lumsden et al, 2020), identifying a possible means to treat sleep disorders after SCI (Scheer et al, 2006).…”
Section: Pineal Glandmentioning
confidence: 99%
“…The pineal gland receives sympathetic innervation from the superior cervical ganglion (SCG). The suprachiasmatic nucleus (SCN) is involved in the control of circadian rhythms and, via sympathetic innervation from the SCG, activates arylalkylamine N-acetyltransferase (AA-NAT) in the pineal gland, which is the main enzyme regulating melatonin synthesis (Lumsden et al, 2020).…”
Section: Norepinephrine Transporter Expression In the Sympathetic Ner...mentioning
confidence: 99%